Enhanced heat transfer performance of optimized micro-channel heat sink via forced convection in cooling metal foam attached on copper plate. (August 2020) - Zhong, Zhaoda; Meng, Like; Li, Xinxi; Zhang, Guoqing; Xu, Yanrou; Deng, Jian
Highlights: The heat sink that comprises metal foams attached to a copper plate was designed and investigated. Three configurations of metal foams used as micro-sized channels to dissipate heat, namely, cube, column, and strip copper foams, were compared in terms of their thermal and flow characteristics. The effects of air speed and proportion of the strip metal foams attached to the copper plate were analyzed. Abstract: The excellent heat transfer performance of open-cell metal foams is well utilized in the thermal management applications. Here, the optimized micro-channel heat sinks were designed based on different metal foams attached on copper plate. The enhanced forced convection by architectural design can result in an increase of the heat transfer performance and flow characteristics, which can be demonstrated by relevant experiments and numerical analysis based on computational fluid dynamics. The results showed that the best heat transfer effect can be obtained at an air velocity of 1.33 m/s and an optimal proportion of 1:1.6 in consideration of power consumption using the strip metal foam attached on copper plate. Moreover, the experiments result is consistent with the numerical simulation. Therefore, our work put forward a facile strategy to optimize the heat transfer performance of micro-channel heat sink via forced convection in cooling metal foam attached on copper plate.